A Rare Tumor with a Very Rare Initial Presentation: Thymic Carcinoma as Bone Marrow Metastasis - Sonam Sharma; Leelavathi Dawson (Hindawi Limited, 2017)
Tumors of thymus gland are rare and account for 0.2% to 1.5% of all the neoplasms. They constitute a heterogeneous group that has an unknown etiology and a complex as well as varied biology. This has led to difficulty in their histological classification and in predicting their prognostic and survival markers. Among them, thymic carcinoma is the most aggressive thymic epithelial tumor exhibiting cytological malignant features and a diversity of clinicopathological characteristics that can cause diagnostic dilemmas, misdiagnosis, and therapeutic challenge. We herein describe a case of a 60-year-old man who while undergoing evaluation for the cause of pancytopenia was discovered having bone marrow metastasis from an asymptomatic thymic carcinoma. Bone marrow metastasis is an extremely rare initial presentation of thymic carcinoma with only few cases reported in the literature.